Attitudes and perceptions of Italian Students in Healthcare Settings on COVID-19 vaccines and vaccinations strategies, one year after the immunization campaign - Bechini, A.; Vannacci, A.; Salvati, C.; Crescioli, G.; Lombardi, N.; Chiesi, F.; Shtylla, J.; Del Riccio, M.; Bonanni, P.; Boccalini, S. (Annali di Igiene Medicina Preventiva e di Comunità, 2024)
Background. The topic of vaccine confidence is increasingly relevant, particularly due to the COVID-19 pandemic and the global distribution of COVID-19 vaccines. This issue is even more critical for students in healthcare settings, given their future role not only as vaccine recipients but also as advocates for vaccination. In light of this, achieving a good level of vaccine acceptance is crucial. Hence, the aim of our study was to evaluate the attitudes and perceptions of healthcare students regarding vaccines and COVID19 vaccination.Methods. Medical and pharmaceutical area students attended an Elective Teaching Activity on COVID-19 vaccines and vaccination campaign, organized at the University of Florence (Italy) and participated in filling two anonymous questionnaires. The first questionnaire was submitted before the Elective Teaching Activity was focused on students’ attitudes and perceptions toward vaccines. The second questionnaire was designed to evaluate the students’ satisfaction with the course topics. Both descriptive and inferential analyses were performed on the results. In addition, the Vaccine Confidence Index was calculated to evaluate the propensity of students toward vaccinations.Results. A total of 423 students attended the Elective Teaching Activity in the early beginnings of 2022. Overall, students have shown greater confidence in vaccines, compared to COVID-19 vaccines, especially as regards the safety profile. Students’ Vaccine Confidence Index was very close to 0.25 value, which indicates being in favor of vaccinations. Nevertheless, in the satisfaction questionnaire filled in at the end of the course, the percentage of students in favor of COVID-19 vaccination increased for both medical (from 94% to 99%) and pharmaceutical area students (from 81% to 97%).Conclusions. Our study suggests that educational activities such as this Elective Teaching Activity, could be considered an effective teaching strategy to improve vaccine acceptance rates among students in healthcare settings.